Questioning Strategy That Works to Foster Critical Thinking Skills: A Study In Islamic University - Fathor Rasyid; Nurul Aini; KJ Varghesse (JEELS (Journal of English Education and Linguistics Studies), 2023)
The aim driving the study is to develop instructional strategies that best fit students to enhance higher order thinking skills through questioning strategy. A university class consisting of thirty students is taking part in the study on Quantitative Research Methodology. The study is classroom action research with two steps. Preliminary study reveals that students had insufficient understanding towards HOTS (Higher Order Thinking Skills) and needed awareness raising towards critical thinking. A questioning strategy-based lesson plan, observation sheets, and critical thinking questionnaire were developed based on a questioning strategy approach. The findings indicate that the questioning strategy significantly enhances critical thinking skills. This result suggests teachers use questioning strategy to assist students' progress critical thinking. The implication of the study is that teachers should have the HOTS to facilitate and cultivate critical thinking among students and establish a thinking-oriented classroom